Dampak Kenaikan Harga Bahan Pokok Terhadap Daya Beli Masyarakat Di Kecamatan Bontomatene Kepulauan Selayar - Andriani; Fitrah Sri Rahayu; Azmiardi Amir Masradin (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to determine the impact of the increase in staple food prices on the purchasing power of residents in Bontomatene District, Selayar Islands. Data collection techniques used in this study were interviews and documentation studies. The data analysis method used was qualitative descriptive analysis. The results of this study indicate that the increase in staple food prices has an impact on the purchasing power of residents in Bontomatene District, Selayar Islands. The impact of the increase in staple food prices has influenced community consumption patterns.